#### Answer

$7$

#### Work Step by Step

$(\sqrt 6 - i)(\sqrt 6+i) = 6 +\sqrt 6i - \sqrt 6i - i^2 = 6 - (-1) = 7$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$7$

$(\sqrt 6 - i)(\sqrt 6+i) = 6 +\sqrt 6i - \sqrt 6i - i^2 = 6 - (-1) = 7$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.